KOMPETENSI PENDIDIK PERSPEKTIF MEMBANGUN PROFESIONALISME GURU - I Wayan Arka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The effort to get quality national education quality requires professional teachers. Building professionalism of teachers is not easy, but it requires special conditions and treatment as well as an ongoing process. As an educational paradigm developer centered on learning, the qualifications and competence of teachers as experts in the position of experts must be one of the main focuses. Teacher positions are professional positions, where a professional position must be supported by professionals who have expertise in their fields. Professionalism must be proven by achieving qualifications, assigning expertise and competence in their fields. Professional teachers are teachers who have the qualifications (Bachelor Degree or Associate's Degree) in the study being taught, and have competence as learning agents. The government has recognized the professionalism of teachers, through the teacher certification program. All teachers must have an educator certificate as a teaching efficiency. Educator certificates can build the quality of education and improve the welfare of teacher corps.Keywords: Teacher, Professionalism, Quality of Education